High-Frequency Motions in the Southeastern South China Sea During Winter–Spring 2018/2019 - Zhang, Zhipeng; Xu, Hongzhou; Vetter, Philip A.; Xie, Qiang; Xie, Xiaohui; Song, Wei; Tian, Chuan (Frontiers in Marine Science, 2021)
High-frequency motions in the southeastern South China Sea (SCS) have rarely been investigated due to sparse field observations. The vertical distribution and temporal variation of internal tides (ITs) and near-inertial waves (NIWs) near the Nansha area in the southeastern SCS were studied using a mooring current dataset from December 2018 to June 2019 in this study. Results showed that ITs were mainly dominated by O1, K1, and M2. Tidal energy analysis indicates that the diurnal ITs were the most energetic components, followed by the semidiurnal ITs. Modal decomposition reveals that diurnal ITs were dominated by mode-3, rather than mode-1, as reported by previous studies. The horizontal kinetic energy (HKE) of diurnal ITs fluctuated within a limited range, almost unaffected by the background field. However, the HKE of semidiurnal ITs was dominated by mode-1 and more affected by the background field, especially at the end of March. Most observations showed the phase of the NIWs propagating upward and the energy propagating downward. During the northeast monsoon period, the near-inertial energy had a large magnitude due to strong wind forcing. In addition, the near-inertial energy peaked from the middle of March to the beginning of April because of the input of NIWs from afar. Overall, near-inertial energy was found concentrated above a 500–600 m depth in the southeastern SCS.